Artifact suppression using cross-circular polarization for millimeter-wave imaging - Qiu, Shuang; Lu, Jian; Zhang, Yongshen; Cheng, Yayun (Frontiers in Physics, 2023)
Millimeter-wave imaging is widely applied to radar detection, personnel security inspection, environmental perception, and so on. Multipath artifact is a common phenomenon in active millimeter-wave (AMMW) imaging and is difficult to be removed. The suppression methods in image reconstruction and post-processing stage are usually complex or time-consuming. This report proposes a cross-polarization method to suppress multipath artifacts between equivalent two-cylinder structures before image reconstruction. The physical mechanisms of co-polarization and cross-polarization imaging are revealed. The suppression effectiveness is demonstrated by conducting W-band AMMW imaging simulation and measurement experiments of a typical multipath scenario at the central frequency of 100GHz (97 103 GHz). The proposed method can directly reconstruct the image with artifact suppression and reduce the pressure of post-processing.